2021
DOI: 10.3389/fimmu.2021.665106
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Antigens (TAAs) for the Serological Diagnosis of Osteosarcoma

Abstract: Osteosarcoma (OS) is the most common form of malignant bone tumor found in childhood and adolescence. Although its incidence rate is low among cancers, the prognosis of OS is usually poor. Although some biomarkers, such as p53, have been identified in OS, the association between the biomarkers and clinical outcome is not well understood. Thus, it is necessary to establish a method to identify patients diagnosed with OS at an early stage. It is becoming obvious that anti-tumor-associated antigens (TAAs) autoant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 95 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…Owing to new adjuvant chemotherapy and improved surgical treatment, the overall survival rate of five-years for osteosarcoma patients has improved up to 70%, while the survival rate of patients with metastasis is still only 10-30% (Ando et al, 2013;Harrison et al, 2018). Several therapeutic approaches have been developed for osteosarcoma in recent years (Li et al, 2021), but their therapeutic effects remain unsatisfactory. In-depth investigations on the molecular mechanisms underlying osteosarcoma metastasis are meaningful for the research of novel treatment approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to new adjuvant chemotherapy and improved surgical treatment, the overall survival rate of five-years for osteosarcoma patients has improved up to 70%, while the survival rate of patients with metastasis is still only 10-30% (Ando et al, 2013;Harrison et al, 2018). Several therapeutic approaches have been developed for osteosarcoma in recent years (Li et al, 2021), but their therapeutic effects remain unsatisfactory. In-depth investigations on the molecular mechanisms underlying osteosarcoma metastasis are meaningful for the research of novel treatment approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies demonstrated that tumor-associated antigens (TAAs) were formed during the autologous cells developing into tumors ( 7 ). Although only trace amounts of TAAs are present in the blood in early-stage lung cancer, these TAAs can be captured by the immune system and lead to the formation of a large amount of specific tumor-associated autoantibodies (AABs) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Osteosarcoma (OS) is the most malignant primary bone tumor originating from primary osteoblasts, which is characterized by the production of osteoid substances. 3 Clinically, osteosarcoma is pathologically characterized by lower limb pain, lumps, anemia, and even toddle. 4 , 5 Although the overall survival rate has been significantly ameliorated due to the early diagnosis and timely treatment, osteosarcoma still remains high mortality in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%